2019
DOI: 10.1016/j.ajur.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with androgen deprivation for hormone sensitive prostate cancer: A new frontier

Abstract: Androgen deprivation therapy (ADT) has been the standard of care for the last 75 years in metastatic hormone sensitive prostate cancer (PCa). However, this approach is rarely curative. Recent clinical trials have demonstrated that ADT combined with other agents, notably docetaxel and abiraterone, lead to improved survival. The mechanisms surrounding this improved cancer outcomes are incompletely defined. The response of cancer cells to ADT includes apoptosis and cell death, but a significant fraction remains v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…We performed an experiment using the SMO inhibitor, vismodegib, to verify that the increased SEMA3C‐induced steroidogenic activities observed in PrSCs is mediated by Shh. Vismodegib is a potent SMO antagonist that inhibits the expression of Hh pathway target genes, such as Gli1 1‐6 . We plated LNCaP Vector and LNCaP SEMA3C cells ( n = 5 each) and PrSCs ( n = 10) in their respective full growth media overnight, then we serum‐starved PrSCs and cultured LNCaP cells in 5% steroid‐depleted CSS containing RPMI media for 72 h. Then, we treated PrSCs with CM‐LN SEMA3C or CM‐LN Vector supplemented with DMSO or vesmodegib (3 nM), in the presence of 1.7 uM DHEA for 72 h. Subsequently, steroid analysis of the conditioned media from treated PrSCs by LCMS showed that vismodegib attenuated the effect of CM‐LN SEMA3C on androgen synthesis in PrSCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed an experiment using the SMO inhibitor, vismodegib, to verify that the increased SEMA3C‐induced steroidogenic activities observed in PrSCs is mediated by Shh. Vismodegib is a potent SMO antagonist that inhibits the expression of Hh pathway target genes, such as Gli1 1‐6 . We plated LNCaP Vector and LNCaP SEMA3C cells ( n = 5 each) and PrSCs ( n = 10) in their respective full growth media overnight, then we serum‐starved PrSCs and cultured LNCaP cells in 5% steroid‐depleted CSS containing RPMI media for 72 h. Then, we treated PrSCs with CM‐LN SEMA3C or CM‐LN Vector supplemented with DMSO or vesmodegib (3 nM), in the presence of 1.7 uM DHEA for 72 h. Subsequently, steroid analysis of the conditioned media from treated PrSCs by LCMS showed that vismodegib attenuated the effect of CM‐LN SEMA3C on androgen synthesis in PrSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Vismodegib is a potent SMO antagonist that inhibits the expression of Hh pathway target genes, such as Gli1. [1][2][3][4][5][6] We plated LNCaP Vector Figure 4A). To validate the activity of vismodegib in blocking Shh signaling pathway in PrSCs, we quantified Gli1 mRNA expression in PrSCs by qPCR ( Figure 4B).…”
Section: Smo Inhibitor Suppressed the Effect Of Sema3c Overexpressimentioning
confidence: 99%
See 1 more Smart Citation
“…Although ∼80% patients initially respond to ADT, incurable castration-resistant PCa develops almost invariably. 207,218,219 Importantly, androgen receptors continue to be critical for PCa growth and progression after ADT. It has been demonstrated that several putative consensus-binding sites for the oncogenic erythroblast transformation specific-related gene (ERG) transcription factor are present in the promoter region of CXCR4; thus, androgen-dependent regulation of ERG could induce CXCR4 expression in PCa cells.…”
Section: Cxcr4/cxcl12 Signaling and Prostate Cancermentioning
confidence: 99%
“…Targeting other potent resistance mechanisms have showed promising results in experimental studies. Dr. David Jarrard and colleagues [7] examined the response to ADT and the putative role of cellular senescence as a biomarker and therapeutic target during ADT. Senescent tumor cells generate a catabolic state with increased glycolysis, protein turnover and other metabolic changes that represent targets for drugs, like metformin, to be applied in a synthetic lethal approach.…”
mentioning
confidence: 99%